A new target for CRP action at the malT promoter. - Menendez, M (1987)
In Escherichia coli, the transcription of the malT gene is activated by the complex formed between cAMP and its receptor protein, CRP. Kinetics of formation of polyribonucleotide products from the corresponding promoter were studied in vitro by two sets of techniques, abortive initiation assays and run-off experiments. The first type of assay indicated that open complexes were formed at malT with an equivalent efficiency, and at comparable rates, whether CRP-cAMP was present or not. Secondary effects due to the activating complex were observed (increased stability of the open complex, elimination of a weaker binding site for the enzyme, improved Michaelis constants of RNA polymerase for the substrates of the assay, UTP in particular). But, primarily, CRP-cAMP did not exert a significant role in the rate of formation of the initiation complex. In contrast, run-off assays showed that the yield of the full-length transcripts was markedly enhanced by prior incubation of the DNA fragment with CRP-cAMP. Both in the presence and in the absence of activator, the rate-limiting step for this process was markedly slower than the formation of the initial open complex. Short oligonucleotides (n less than 9), probably arising from a recycling process, were found when the initiation complex was formed in the absence of CRP-cAMP. They were abolished by prior incubation with the activator. Unexpectedly, CRP-cAMP appears to favour the escape of RNA polymerase from the initiation complex at this promoter.